CYTOTOXIC AND ANTIOXIDANT ACTIVITY OF FRUIT JUICE OF ERIOBOTRYA JAPONICA (THUNB.) LIND PLANT CULIVATED IN IRAQ - .Alwash, B.M.J (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to evaluate the anticancer effect of Eriobotrya japonica (loquat) fruit juice on cancer cell lines (in vitro) and its antioxidant activity. Study was performed on two cancer cell lines, human cervical cancer (Hela), rhabdomyo sarcoma (RD), and rat embryogenic fibroblast (REF) as a normal cell, at concentrations of 62.5, 125, 250, 500 and 1000 µg/ml of fruit juice were measured at 24, 48, and 72-hr. with three replicates. Free radical 1,1Dyphenyl-2-picrylhydrazyl radical (DPPH) was used for testing the ability as antioxidant on 25, 50, 75, 100, 150 µg/ml concentration of the loquat fruit juice. The results revealed that the  juice  of   E.  japonica had high antioxidant influence (100%) in 150 µg/ml concentration, followed by 88% in 100 µg/ml concentration. Effect of growth inhibition of cancer cells was depended on juice concentration. The effect of juice on Hela cell line was more than on RD, while the highest effect of juice  on Hela was shown on  concentration of 500 µg/ml the 48 hr. The cytotoxic effect of  exhibited that had a significant effect  (P